Factors influencing performance and injury risk in elite female gaelic team sport players and future research directions: a narrative review - Duggan, J. D.; Collins, K.; Keane, K. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Sports science research in elite female Gaelic team sports has increased in recent years, but still a large disparity exists between the volume of studies involving male and female players. As a consequence of this, it is difficult for practitioners to develop an evidence-based approach when working with female players.